Green Economy Transition Strategy in Regional Development, A Study of Energy Efficiency and Social Inclusion in Makassar - Tahir, Tahir; Jumarding, Ahmad (Yayasan Riset dan Pengembangan Intelektual, 2025)
The transition toward a green economy in urban areas requires the integration of energy efficiency and social inclusion as two fundamental pillars of sustainable development. Makassar City, as the economic center of Eastern Indonesia, is experiencing increasing energy consumption, environmental pressures, and widening social disparities, necessitating a well-directed transition strategy supported by empirical evidence. This study aims to analyze the conditions and challenges of energy efficiency, identify the level of social inclusion within green development programs, and formulate an integrative strategy that can be implemented by local governments. A qualitative approach was employed through in-depth interviews, observations, and document analysis involving various stakeholders, including government institutions, environmental NGOs, academics, and vulnerable community groups. The findings indicate that energy efficiency programs in Makassar remain in the early stages of implementation and are dominated by top-down approaches, thereby failing to generate substantial changes within household and MSME sectors. Social inclusion is also found to be limited, as evidenced by the lack of participation from vulnerable groups in the planning and evaluation processes of green development initiatives. Moreover, weak cross-sectoral coordination has resulted in energy policies and social policies operating independently, hindering the effectiveness of a comprehensive green economy transition. The study formulates an integrative strategy combining institutional strengthening, expanded access to energy-efficient technologies, enhanced community energy literacy, and reinforced participatory mechanisms as pathways toward a low-emission and socially equitable regional development framework. These findings are expected to provide substantive contributions to local energy policy formulation and enrich the scientific literature on urban green economy transitions in Indonesia.